Association of single nucleotide polymorphisms within cytokine genes with juvenile idiopathic arthritis in the Czech population - Cinek, Ondrej; Vavrincová, Pavla; Striz, Ilja; Drevínek, Pavel; Sedláková, Pavlína; Vavrinec, Jan; Slavcev, Antonij (The Journal of rheumatology, 2004)
OBJECTIVE: To examine the possible association of juvenile idiopathic arthritis (JIA) with polymorphisms within cytokine genes in the Czech population. METHODS: In a case-control study, genotypes of 130 patients with JIA (63 male, 67 female; age at onset 7.6 +/- 4.4 yrs; 43 oligoarticular, 72 polyarticular, 15 systemic form) were compared to 102 healthy unrelated blood donors. Using the polymerase chain reaction technique with sequence-specific primers from the 13th IHWG workshop, we analyzed 19 single nucleotide polymorphisms within 12 different cytokine genes [interleukin (IL)-1a, IL-1beta, IL-2, IL-4, IL-6, IL-10, IL-12, transforming growth factor (TGF)-beta, interferon (IFN)-g], and related molecules (IL-1R, IL-1RA, IL-4Ra). Genotype frequencies were compared using chi-square analysis, and the significance level was corrected for the number of independent tests. RESULTS: Significant positive association was found for the G allele of the IL-4 -1098 T/G polymorphism, which was carried by 10% of cases and 25% of controls [odds ratio (OR) 0.32, 95% confidence interval (CI) 0.16-0.67, corrected p = 0.038). Also, a nonsignificant increase in the frequency of the IL-1beta +3962 C allele was detected in cases (96%) versus controls (84%) (OR 4.65, 95% CI 1.64-13.2, corrected p = 0.091). We did not replicate previously found associations with the IL-1a, IL-6, IL-10, and IL-1RA polymorphisms. CONCLUSION: Our study showed association with JIA for the IL-4 -1098 T/G polymorphism. It also underlines the genetic contribution of IL-1 polymorphisms to the pathogenesis of JIA, as another polymorphism within the IL-1beta may influence the risk of the disease.
Keywords: Polymorphism, Single Nucleotide; Humans; lidé středního věku; dítě; Child; cytokiny; jednonukleotidový polymorfismus; Female; dospělí; Genotype; lidé; Adult; juvenilní artritida; ženské pohlaví; Male; Middle Aged; Arthritis, Juvenile; Adolescent; genetická predispozice k nemoci; Genetic Predisposition to Disease; Czech Republic; Cytokines; genotyp; Česká republika; mužské pohlaví; mladiství